2012
DOI: 10.1134/s1068162012040127
|View full text |Cite
|
Sign up to set email alerts
|

Oligomerization of site-specific nicking endonuclease BspD6I at high protein concentrations

Abstract: Ability of site-specific nickase BspD6I (Nt.BspD6I) to oligomerize at concentrations > or = 0.5 microM (> or = 0.035 mg/mL) is studied. Three states of Nt.BspD6I are registered via electrophoretic studies both in the presence and in the absence of DNA. Estimation of their molecular mass allows assigning them as a monomer, a dimer and a trimer. Both dimeric and monomeric Nt.BspD6I are shown to hydrolyze its DNA substrate with the identical specificity. Calculation of the electrostatic potential distribution on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…7) observed after applying 1 μM of Nt.BspD6I. It is previously shown, that Nt.BspD6I is able to oligomerize at concentrations higher than 0.5 μM [31]. Using the frequency change of 200 Hz and molecular weight of Nt.BspD6I (70.8 kDa) the surface concentration of NE can be estimated according to Eq.…”
Section: Nicking Endonuclease Bspd6i Binding With Dna Fragment That Imentioning
confidence: 99%
See 1 more Smart Citation
“…7) observed after applying 1 μM of Nt.BspD6I. It is previously shown, that Nt.BspD6I is able to oligomerize at concentrations higher than 0.5 μM [31]. Using the frequency change of 200 Hz and molecular weight of Nt.BspD6I (70.8 kDa) the surface concentration of NE can be estimated according to Eq.…”
Section: Nicking Endonuclease Bspd6i Binding With Dna Fragment That Imentioning
confidence: 99%
“…However, the fact of Nt.BspD6I complex formation with product of its DNA hydrolysis was demonstrated by both approaches. It was previously shown that Nt.BspD6I possesses the ability of nonspecific DNA binding [31]. To assess the extent of such non-specific binding with DNA, we analyzed the hydrolysis of duplex IV that contained fluorescent label TAMRA on the 3′-end of its top strand in the presence of different competitors: canonical duplex I-F, duplex I-G that corresponds to the product of hydrolysis by Nt.BspD6I, and 30-bp non-specific duplex III without the Nt.BspD6I recognition site (Fig.…”
Section: Nicking Endonuclease Bspd6i Binding With Dna Fragment That Imentioning
confidence: 99%
“…Nt.BspD6I and ss.BspD6I were expressed and purified separately following the protocols described in refs. [ 51 , 53 , 54 ]. Modified oligodeoxyribonucleotides were synthesized by the standard solid-phase approach using commercially available phosphoramidites (according to the protocols provided by manufacturers), then purified by reverse-phase high-performance liquid chromatography (RP-HPLC) and characterized as described earlier [ 55 ].…”
Section: Methodsmentioning
confidence: 99%
“…It has been established by an electrophoretic mobility shift assay [47] that Nt.BspD6I has high affinity for non-specific DNA duplexes. It was shown in refs.…”
Section: Kinetics Of Non-specific Ntbspd6i Binding To Dnamentioning
confidence: 99%